Finite element analysis of the deformation behavior of a thin flexible substrate due to thermal loading - Zuñega, Jonee Christine P. (2006)
The use of thin flexible substrates to maximize production capacity in high interconnect applications has posed many challenges in its assembly process. Gross deformations have been observed in most assembly processes that subject the substrate to drastic temperature changes translating to thermomechanical deformation. The cyclic rise and fall in temperature has a corresponding deformation owing to the highly temperature dependent material properties of the polymers comprising the substrate which is coupled by polymer polymer and metal polymer interactions during the heating and cooling cycles. This paper presents the results of a study towards fundamental understanding of the thermomechanical behavior of flex substrates to facilitate innovative ways to mitigate the problem. It investigates the effect of temperature and the differences in the heating and cooling rates on the deformation behavior of the flexible substrate which is mostly encountered in its assembly process. A finite element analysis (FEA) was done to model the deformation of the substrate and understand the mechanisms underlying it. The modeling assumptions were validated using a temperature dependent Shadow Moire technique which measured the deformation profile of the substrate when subjected to actual process temperatures. The results of the modeling strategy gave very good correlation with measurements using Shadow Moire technique and oven experiments. Furthermore, with the modeling strategy established, results of two dimensional and three dimensional FEA were analyzed using a 23 full factorial experimental design to determine the modulating factors responsible for the thermomechanical deformation of the substrate and their possible interactions. This experimental design conveniently evaluated the relative magnitudes of the predicted FEA effects of the following factors: layer stack up symmetry, presence of polymer-metal and polymer-polymer adjacent materials on the flex substrate layout and the inclusion of a substrate metal carrier that holds the substrate in place. Results indicate that the largest contributor to the deformation based on FEA is the layer stack up symmetry. There is also a major interaction between layer stack-up symmetry and the frame carrier. Both account for about 61% of the variation in the predicted maximum out of plane displacement response. From the results, deformation is mitigated when symmetry is present and use of a frame carrier can be a big factor to control deformation in the absence of symmetry. The study also includes the other interaction effects among the three factors and the impact of local versus global mismatch of substrate properties